THE INFLUENCE OF THE STEAM LEARNING MODEL ON MOTIVATION AND RESULTS IN SCIENCE LEARNING IN CLASS V STUDENTS - Maya Safitri; Nurlina Nurlina; Hartono Bancong (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2023)
The study's objective was to determine how the STEAM Model affected fifth-graders at SDI Biringkaloro Gowa's science learning results and motivation. This type of research is essentially an experiment. In this study, the quasi-experimental design takes the shape of a quantitative study with the kind of quasi-experimental research, where the design has a control group but can't fully function to control outside factors that influence how the experiment is carried out. The experimental group and the control group were the two groups used in this investigation. There are 60 students involved as the sample in this study. The 30 students as experimental group or class will employ the STEAM learning model, while the control class which includes the other 30 students will conduct the learning without using the STEAM learning model. The data were investigated using statistical analysis techniques such as validity analysis, descriptive statistical analysis, and inferential statistical analysis. The data was processed using the IBM SPSS 27 application. Homogeneity, normality, and MANOVA hypothesis testing were among the tests performed. According to an examination of the Manova test findings, which indicated a significant value of 0.000, the STEAM learning model has an effect on the motivation and academic performance of fifth grade students at SDI Biringkaloro Gowa. H0 is rejected and Ha is acceptable if 0.000 0.05. This suggests that the STEAM learning paradigm's implementation at SDI Biringkaloro Gowa has a significant impact on students' motivation and science learning outcomes.